2013
DOI: 10.1080/10410236.2013.824063
|View full text |Cite
|
Sign up to set email alerts
|

Scaring the Snus Out of Smokers: Testing Effects of Fear, Threat, and Efficacy on Smokers’ Acceptance of Novel Smokeless Tobacco Products

Abstract: Novel smokeless tobacco products (such as snus) are aggressively promoted to smokers by the tobacco companies. The Extended Parallel Process Model (EPPM; Witte, 1992) was used to evaluate the current perceptions of threat, efficacy, attitudes, and behavioral intentions regarding snus in a nationally representative sample of 1,836 smokers. Participants were then exposed to messages designed to discourage smokers from trying snus. On average, smokers perceived health threats of snus as somewhat serious, but beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…3,4,15,24 Instead of education being ineffective, as suggested by some, it may be improperly implemented or may require supplemental programs6 such as information campaigns that remind and trigger individuals to perform a certain behavior. 18 Interventions using fear to educate, inform, and motivate desirable health behaviors have attracted substantial academic and practitioner interest, [25][26][27][28][29][30][31] including in the context of farm safety. 23,24,[32][33][34] For example, the Health and Safety Authority in Ireland used fear to urge farmers to stop taking risks, with the message 'My farm accident didn't kill me, unlike the 22 people who died on Irish farms last year'.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,15,24 Instead of education being ineffective, as suggested by some, it may be improperly implemented or may require supplemental programs6 such as information campaigns that remind and trigger individuals to perform a certain behavior. 18 Interventions using fear to educate, inform, and motivate desirable health behaviors have attracted substantial academic and practitioner interest, [25][26][27][28][29][30][31] including in the context of farm safety. 23,24,[32][33][34] For example, the Health and Safety Authority in Ireland used fear to urge farmers to stop taking risks, with the message 'My farm accident didn't kill me, unlike the 22 people who died on Irish farms last year'.…”
Section: Introductionmentioning
confidence: 99%
“…The current study contributes to the fear appeal scholarship as it treats threat and fear as two distinct constructs, thus bringing the mediating role of fear on individuals' risk estimation to the forefront of fear appeal research. As Popova [30] argued, "threat is a cognitive assessment, while fear is an emotional response evoked by some stimulus" (p. 932). The finding of the current study is generally in line with Popova's [30] result while some differences exist.…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical research has provided support to this notion. For example, Popova [30] applied the EPPM to a novel smokeless tobacco product setting, and found that when efficacy is high, higher levels of threat were effective in message acceptance. In this study, the threat and efficacy were both measured as existing individual variables.…”
Section: Efficacy As An Existing Individual Variable In the Eppmmentioning
confidence: 99%
“…Adults with access to the electronic media in their homes were more likely to have knowledge about the health hazards of tobacco consumption. These gaps in the reach of antitobacco messaging argued for the need to direct anti-tobacco campaigns more aggressively to users of smokeless tobacco (Popova, 2014), especially women, and to those who do not have electronic media in their homes. This study shows that education plays a significant role in influencing adults to pay attention to anti-tobacco messages and in improving their awareness.…”
Section: Discussionmentioning
confidence: 99%